Low temperature, solution processed spinel NiCo2O4 nanoparticles as efficient hole transporting material for mesoscopic n-i-p perovskite solar cells. (15th January 2020) - Bashir, Amna; Shukla, Sudhanshu; Bashir, Rabia; Patidar, Rahul; Bruno, Annalisa; Gupta, Disha; Satti, Muhammad Sultan; Akhter, Zareen
Highlights: First demonstration of NiCo2 O4 for efficient hole extraction and moisture resistant layer in PSCs using triple cation perovskite material. Solar to power conversion efficiency (PCE) > 16% is achieved using NiCo2 O4 comparable to the standard devices containing spiro-OMeTAD as HTL. Detailed degradation analysis of the cells showed significant improved stability of devices, providing direction towards stable and low-cost cells for commercial relevance. Fundamental insights of the charge transfer and recombination process at perovskite- NiCo2 O4 interface enables better understanding of designing perovskite solar cells. Abstract: Spinel Nickel cobaltite oxide (NiCo2 O4 ) have received great interest due to its usage in several industrial applications. The motivation of the present study is to explore the usefulness of spinel Nickel cobaltite oxide as inorganic charge transporting layer for standard perovskite solar cells (PSCs). This is the first demonstration of successful use of NiCo2 O4 nanoparticles as hole transporting layer (HTL) in standard PSCs with the triple cation perovskite material. The synthesis of nanoparticles was done using a facile chemical precipitation method without the use of surfactant. The synthesized nanoparticles were characterized by the various techniques like X-ray diffraction (XRD), X-ray absorption spectroscopy (XAS), Field emission scanning electron microscopy (FE-SEM), and UV–vis spectroscopy (UV–vis). The co-ordination of Ni in Co3 O4 matrix, as well as M +n O bond lengths, were confirmed by the XAS studies. The standard mesoporous PSCs were fabricated by spin-coating a thin layer of NiCo2 O4 (120 nm), and fabricated PSCs show an esteemed power conversion efficiency (PCE) of >14% (under standard illumination conditions) and long-term stability (under ambient condition RH = 30–40%) as compared to the spiro-based PSCs. To improve the device performance further we also fabricated the PSCs using the interfacial hole transporting layer, presenting a PCE of >16% with almost negligible hysteresis that is comparable to the normal standard PSCs based on spiro-OMeTAD as HTL. The performance of PSCs was further analysed by Electrochemical Impedance Spectroscopy (EIS), Photoluminescence (PL), Time-resolved Photoluminescence (TrPL) studies. The results showed the reduced recombination resistance in the PSCs using NiCo2 O4 as well as interfacial layer. These outcomes indicate the effectiveness of NiCo2 O4 interlayer for stable and highly efficient perovskite solar cells.